2014
DOI: 10.1186/2050-7283-2-10
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the prevention program ‘New Perspectives’ (NP) on juvenile delinquency and other life domains: study protocol for a randomized controlled trial

Abstract: BackgroundNew Perspectives (NP) is a prevention program aiming to prevent that youth at onset of a criminal career will develop a persistent criminal behaviour pattern. The effects of NP on juvenile delinquency and other life domains are investigated, using a randomized controlled trial (RCT).Method/DesignIn the present study at-risk youth aged 12 to 23 years are assigned randomly to the intervention (N = 90, NP) or control condition consisting of care as usual (N = 90, CAU). After screening, random assignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…Self-report follow-up data of adolescents were collected 12 months after completion of the intervention. A more elaborate description of the recruitment and randomization process can be found in prior studies of De Vries, Hoeve, Assink, et al (2014 ; De Vries, Hoeve, Wibbelink, et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-report follow-up data of adolescents were collected 12 months after completion of the intervention. A more elaborate description of the recruitment and randomization process can be found in prior studies of De Vries, Hoeve, Assink, et al (2014 ; De Vries, Hoeve, Wibbelink, et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…NP is culturally responsive in that adolescents who receive NP are assigned to a social worker with similar ethnic background. More information regarding core components of the NP program can be found in the prior studies of De Vries, Hoeve, Assink, et al (2014 ; De Vries, Hoeve, Wibbelink, et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The social care practitioners serve on a 7/24 schedule, and their services include setting goals together with the youngster, challenging tough issues with knowledge, confidence and skill, coaching, motivational interviewing for smooth behavior modification, strengthening ties with the social support systems by involvement of parents, friends and teachers, helping with cognitive restructuring, teaching problem-solving skills, and role-modeling. Earlier empirical NP studies revealed positive changes in parenting, social relationships and crime involvement attitudes and behavior (De Vries et al, 2014).…”
Section: Age-graded Theory Of Informal Social Controlmentioning
confidence: 98%
“…Considering the expensiveness of both comprehensive rehabilitation and detention of delinquents in correctional centers, empowering evidence-based prevention programs well before a long-lasting and persistent criminal career begins would be a contribution to society (De Vries et al, 2014). If the objective of policy makers and practitioners is substantial behavioral change in the desired direction, prevention and interventions should be based on rigorous research outcomes of sound theories in the related fields (Hoeve et al, 2009;Kazdin, 2001).…”
Section: Age-graded Theory Of Informal Social Controlmentioning
confidence: 99%
See 1 more Smart Citation